Aptamer-Conjugated Quantum Dot Optical Biosensors: Strategies and Applications - Dongmin Kim (MDPI AG, 2021)
Quantum dots (QDs) represent the promising new generation of luminophores owing to their size-, composition-, and surface-dependent tunable photoluminescence (PL) and photochemical stability. The development of various QD composites with high PL and good biocompatibility has facilitated the use of aptamer-functionalized QD biosensors for highly sensitive and specific detection of molecules in clinical and environmental settings. In addition to describing the recent advances in aptamer-based QD biosensor technology for the detection of diverse chemicals and biomolecules, this review provides recent examples of sensing strategies based on optical signal enhancement and quenching of QDs. It also discusses potential strategies for the development of biosensors to widen their practical applications across various scientific and technological fields.